Strengthening pathogen genomic surveillance for health emergencies: insights from the World Health Organization’s regional initiatives - Akande, Oluwatosin Wuraola; Carter, Lisa L.; Abubakar, Abdinasir; Achilla, Rachel; Barakat, Amal; Gumede, Nicksy; Guseinova, Alina; Inbanathan, Francis Yesurajan; Kato, Masaya; Koua, Etien; Leite, Juliana; Marklewitz, Marco; et al. (Frontiers in Public Health, 2023)
The onset of the COVID-19 pandemic triggered a rapid scale-up in the use of genomic surveillance as a pandemic preparedness and response tool. As a result, the number of countries with in-country SARS-CoV-2 genomic sequencing capability increased by 40% from February 2021 to July 2022. The Global Genomic Surveillance Strategy for Pathogens with Pandemic and Epidemic Potential 2022–2032 was launched by the World Health Organization (WHO) in March 2022 to bring greater coherence to ongoing work to strengthen genomic surveillance. This paper describes how WHO’s tailored regional approaches contribute to expanding and further institutionalizing the use of genomic surveillance to guide pandemic preparedness and response measures as part of a harmonized global undertaking. Challenges to achieving this vision include difficulties obtaining genomic sequencing equipment and supplies, shortages of skilled staff, and obstacles to maximizing the utility of genomic data to inform risk assessment and public health action. WHO is helping to overcome these challenges in collaboration with partners through a harmonized programme of work at the global, regional, and country levels. Through its global headquarters, six regional offices, and 153 country offices, WHO is providing support for country-driven efforts to strengthen genomic surveillance in its 194 Member States, with activities reflecting regional specificities. WHO’s regional offices serve as platforms for those countries in their respective regions to share resources and knowledge, engage stakeholders in ways that reflect national and regional priorities, and develop regionally aligned approaches to implementing and sustaining genomic surveillance within public health systems.